Foundations of soft case-based reasoning - Pal, Sankar K. (Wiley series on intelligent systems., 2004)
* Provides a self-contained description of this important aspect of information processing and decision support technology.* Presents basic definitions, principles, applications, and a detailed bibliography.* Covers a range of real-world examples including control, data mining, and pattern recognition.